Glycolysis Is Required for LPS-Induced Activation and Adhesion of Human CD14+CD16− Monocytes - Lee, Man K. S.; Al-Sharea, Annas; Shihata, Waled A.; Bertuzzo Veiga, Camilla; Cooney, Olivia D.; Fleetwood, Andrew J.; Flynn, Michelle C.; Claeson, Ellen; Palmer, Clovis S.; Lancaster, Graeme I.; Henstridge, Darren C.; Hamilton, John A.; et al. (Frontiers in Immunology, 2019)
Monocytes in humans consist of 3 subsets; CD14+CD16- (classical), CD14+CD16+ (intermediate) and CD14dimCD16+ (non-classical), which exhibit distinct and heterogeneous responses to activation. During acute inflammation CD14+CD16- monocytes are significantly elevated and migrate to the sites of injury via the adhesion cascade. The field of immunometabolism has begun to elucidate the importance of the engagement of specific metabolic pathways in immune cell function. Yet, little is known about monocyte metabolism and the role of metabolism in mediating monocyte activation and adherence to vessels. Accordingly, we aimed to determine whether manipulating the metabolism of CD14+CD16- monocytes alters their ability to become activated and adhere. We discovered that LPS stimulation increased the rate of glycolysis in human CD14+CD16- monocytes. Inhibition of glycolysis with 2-deoxy-D-glucose blunted LPS-induced activation and adhesion of monocytes. Mechanistically, we found that increased glycolysis was regulated by mTOR-induced glucose transporter (GLUT)-1. Furthermore, enhanced glycolysis increased accumulation of reactive oxygen species (ROS) and activation of p38 MAPK, which lead to activation and adhesion of monocytes. These findings reveal that glycolytic metabolism is critical for the activation of CD14+CD16- monocytes and contributes to our understanding of the interplay between metabolic substrate preference and immune cell function.